Factors Related To HPV Vaccine Practice Among Adult Women - Adelia Perwita Sari; Fariani Syahrul (Jurnal Berkala Epidemiologi, 2014)
Cervical cancer is one of the most common cancers in women in the world. Cervical cancer can be effectively prevented by human papillomavirus (HPV) vaccination. Unfortunately, HPV vaccination coverage is still very low. The purpose of this study was to analyze the factors underlying HPV vaccination in adult women. This study uses a case-control design with a sample size of 25 in each case and control group. Case samples were women who did HPV vaccinations at Indonesian Midwives Association, Kediri City, while control samples were neighboring cases that did not carry out HPV vaccinations. The independent variables are age, education level, marital status, income level, knowledge, family support, family history of cervical cancer and the dependent variable is HPV vaccination. Data processing using Chi-Square or Fisher's Exact analysis with a significance level of 95%. The results showed that there was a relationship between education level (p = 0.006; c = 0.346), level of knowledge (p = 0.001; c = 0.464), and family support (p = 0,000; c = 0.516) and HPV vaccination measures. While the variables not related to HPV vaccination are age (p = 0.275), marital status (0.495), income level (0.098) and family history of cervical cancer (p = 1,000) with HPV vaccination. Based on the results of the study it can be concluded that family support and level of knowledge are factors that are quite strongly associated with HPV vaccination in adult women. Interventions, therefore, are focused on increasing knowledge for women and their families.